2012
DOI: 10.3109/14767058.2012.715436
|View full text |Cite
|
Sign up to set email alerts
|

A metabolomic study of preterm human and formula milk by high resolution NMR and GC/MS analysis: preliminary results

Abstract: The preliminary results of this study suggest that metabolomics may provide a promising tool to study aspects related to the nutrition and health of preterm infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 22 publications
1
85
0
1
Order By: Relevance
“…Finally, metabolomics analysis is also applicable to food itself to identify major nutritional constituents and/or particular metabolites showing significant bioactivity, including milk, cereals, wine, fruits, vegetables, and meat (13). This is of particular relevance for the analysis of breast milk (14) in order to explore the relationship among mother's nutrition, breastfeeding, and child's nutrition for optimal growth and development. Human milk varies in composition, time, and volume, and is the first source of nutrient for the newborn.…”
Section: Metabolomics Technologies In Clinical Studiesmentioning
confidence: 99%
“…Finally, metabolomics analysis is also applicable to food itself to identify major nutritional constituents and/or particular metabolites showing significant bioactivity, including milk, cereals, wine, fruits, vegetables, and meat (13). This is of particular relevance for the analysis of breast milk (14) in order to explore the relationship among mother's nutrition, breastfeeding, and child's nutrition for optimal growth and development. Human milk varies in composition, time, and volume, and is the first source of nutrient for the newborn.…”
Section: Metabolomics Technologies In Clinical Studiesmentioning
confidence: 99%
“…The application of metabonomics analysis is well suited for neonatal metabolic research due to the simple, safe, and noninvasive approach that can be deployed on urine and stool samples (21,24). In particular, promising metabolic insights into urine (20) and also into human breast milk (25) have led to a rapid expansion of the field of clinical applications of metabolomics in neonatology (26). Such data will serve as a reference to provide understanding of metabolic processes involved in developmental physiology, metabolic programming, and nutritional requirements.…”
mentioning
confidence: 99%
“…Three of these studies are summarized in Table 1. Using high-resolution ÂčH-NMR and GC-MS, Marincola et al (2012) identified differences in metabolite composition between pre-term human BM and infant formula milk (FM). In this study, lactose was found to be higher in pre-term BM compared to FM.…”
Section: Recent Investigations Into the Breastmilk Metabolomementioning
confidence: 99%